Effects of Bulk Wave Radiation on IDT Admittance on 42°YX-LiTaO3 - Hashimoto, Ken-ya; Yamaguchi, Masatsune; Kovacs, Günter; Wagner, Karl Christian; Ruile, Werner; Weigel, Robert (IEEE Transactions on Ultrasonics Ferroelectrics and Frequency Control, 2001)
This paper investigates the effects of bulk acoustic wave (BAW) radiation on the admittance of interdigital transducers (IDTs) with significant internal reflections of shear horizontal (SH) type leaky surface acoustic waves (SAWs) on 42 YX-LiTaO3 (42-LT). Theoretical analysis is made by using the discrete Green function theory, and synchronous one-port resonators are analyzed. It is shown that the BAW radiation significantly affects the IDT characteristics even for resonators; under certain circumstances, BAWs launched from an IDT are converted into SH-type SAWs by the strong internal reflections, and they interact with the BAWs radiated by the IDT. Then, the net amount of the radiated BAW power is highly dependent upon the number of IDT finger pairs. For the precise simulation of devices based on the SH-type SAWs with strong internal reflections, the BAW radiation should carefully be taken into consideration. If the BAW radiation is ignored, the radiated power of the SH-type SAWs may seem to be negative above the BAW cut-off frequency
elib2cris::1512001600,hashimoto2001
Keywords: Surface acoustic waves; Sawing machines; Permittivity; Green function; Fingers; Gratings; Admittance; Cutoff frequency; Acoustic reflection; Acoustic waves